MARKETING STRATEGIES IN INCREASING TURNOVER OF SALES OF PROCESSED TEMPE CRIPICS MSMEs IN CILACAP - Zahro, Desi Unaisatus; Saksana, Joned Ceilendra (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2025)
MSMEs or Micro, Small and Medium Enterprises are the main pillars that can restore growth during the economic crisis in Indonesia. That way, MSMEs need to implement a marketing strategy in their business to increase sales turnover. Marketing Mix or what is known as 4P (product, price, place, promotion) is a strategy that can be applied to every business actor as a basic element for running their business so that sales on the market can produce better results. For this reason, this research aims to find out whether the marketing strategy at the Kripik Tempe Family MSME can increase its product sales turnover. The method used in this research is a descriptive qualitative method to analyze field conditions in a structured, objective, thorough manner so that a conclusion can be drawn that a marketing strategy marketing mix method can be applied to the MSME Chips Tempe Family and can be analyzed using SWOT (strength). , weaknesses, opportunities, arts) which aims to increase sales turnover.